PENGEMBANGAN INSTRUMEN HASIL BELAJAR FISIKA PESERTA DIDIK KELAS XI IPA SMA NEGERI 1 DONRI-DONRI KABUPATEN SOPPENG - Syamsuddin, Mulyani (Universitas Negeri Makassar, 2017)
This study aims at describing the development of Physics learning result instrument of class XI IPA (Science) at SMAN 1 Donri-Donri in Soppeng district based on face validity, content validity, level of difficulties, items distinction power, deceiver effectiveness, items validity, and reliability. This study is a research and development. The subjects were all 113 students of class XI IPA. The data collection in this study was conducted using test technique. Data was analyzed by employing quantitative descriptive analysis. The result of the study show that: Physics learning result instrument which consists of 45 item of questions given to the students of class XI IPA has already met the aspect of face validity so it can be used to measure the studentsâ€™ Physics learning outcomes for class XI IPA. Physics learning result instrument which consist of 45 items of questions given to the students of class XI IPA has already met the aspect of content validity so it can be used to measure standardÂ competence, based competence, and indicators that appropriate with Physics material. Physics learning result instrument which consist of 42 items of questions given to the students of class XI IPA has already fulfilled the standard with 8 difficult items, 32 adequately difficult items, and 3 easy items. Physics learning result instrument which consist of 42 items of questions given to the students of class XI IPA has good deceiver which are working for all items. Physics learning result instrument which consist of 42 items of questions given to the students of class XI IPA has good items validity for all items. Physics learning result instrument which consist of 42 items of questions given to the students of class XI IPA is reliable.